Computational analysis of 3D-flows in rocket produced H2/H2O plasma based MHD generators for space applications. (1st January 2013) - Saurabh, Ayush; Turan, Ali
In this paper, a study is presented in which the magnetohydrodynamic interactions have been analysed in Faraday connection generators, which show potential for space applications. The channel design of an extensively studied Sakhalin generator developed in the former USSR has been used and coupled with a cesium seeded liquid hydrogen and liquid oxygen combustion based chemical rocket. The CFD analysis of this design has been done using a program code based on multigrid algorithms for the solution of momentum and electrical equations. The code implements corrections in k-epsilon turbulence equations and for the calculations of transport properties of the plasma. The development of the secondary flows with complicated six vortex cells in the MHD channel has been analysed, which show agreement with a previous experimental study. Also, it has been shown that power output of the MHD generator could be significantly improved by changing the configuration of the MHD channel.